Adiponectin as a potential marker of prostate cancer progression: studies in organ-confined and locally advanced prostate cancer - Housa, D; Vernerová, Z; Heráček, J; Procházka, B; Čechák, P; Kuncová, J; Haluzík, M (Physiological research, 2008)
Serum levels of adiponectin were measured in patients with benign prostatic hyperplasia and prostate cancer of pT2 and pT3 stage. Adiponectin ELISA assay, immunohistochemistry, and selected metabolic and biochemical parameters measurement was performed in 25 patients with benign prostatic hyperplasia and 43 with prostate cancer (17 patients with organ-confined and 26 patients with locally advanced disease). Serum adiponectin levels did not differ between prostate benign hyperplasia and cancer clinical stage T2, but was significantly higher in pT3 relative to pT2 group (14.51+/-4.92 vs. 21.41+/-8.12, P = 0.003). Tissue immunohistochemistry showed enhanced staining in neoplastic prostate glands and intraepithelial neoplasia relative to benign prostatic hyperplasia without distinction between disease grade and stage. Serum adiponectin levels are higher in locally advanced relative to organ-confined prostate cancer and may thus serve as an auxiliary marker providing further improvement for discrimination between pT2 and pT3 stages.
Keywords: Prostatic Neoplasms; nádory prostaty; Humans; hyperplazie prostaty; lidé středního věku; Biomarkers, Tumor; Aged; ELISA; Neoplasm Invasiveness; senioři; lidé; Immunohistochemistry; imunohistochemie; Enzyme-Linked Immunosorbent Assay; Prostatectomy; Prostatic Hyperplasia; nádorové biomarkery; staging nádorů; Male; Middle Aged; Adiponectin; adiponektin; invazivní růst nádoru; Neoplasm Staging; prostatektomie; mužské pohlaví